Factors influencing customer acceptance on Ar Rahnu Islamic pawn broking scheme: a study on Bank Rakyat Precinct 15, Putrajaya / Nur Amirah Abu Hassan - Abu Hassan, Nur Amirah (2015)
The main objective of this study is to determine the factors that influencing customer acceptance towards Ar Rahnu Islamic pawn broking scheme in Bank Rakyat Precinct 15, Putrajaya. This study also will determine the relationship between pricing system, locality, Shariah view and customer acceptance towards Ar Rahnu Islamic pawn broking scheme among the customers of Bank Rakyat Precinct 15, Putrajaya. Besides that, this study will investigate what is the most significant relationship between pricing system, locality, Shariah view and customer acceptance towards Ar Rahnu Islamic pawn broking scheme among the customers of Bank Rakyat Precinct 15, Putrajaya. In this study, 100 respondents are being chosen by using convenience sampling method. Primary data will be used which is by distributing questionnaire to the respondents. The findings in this study were being tested by reliability analysis which showed that all the independent variables has a good reliability questions since the Cronbach’s Alpha in more than 0.6. Furthermore, the Pearson correlation revealed that all the independent variables which are pricing system, locality, and Shariah view are positively and moderate relationship with dependent variable which is customer acceptance. Moreover, this study concludes that Shariah view and pricing system are the factors influencing the customer acceptance towards Ar Rahnu Islamic pawn broking scheme in Bank Rakyat Precinct 15, Putrajaya.